Ultrasound Deep Brain Stimulation Regulates Food Intake and Body Weight in Mice - Wen Meng; Zhengrong Lin; Tianyuan Bian; Xiaoyan Chen; Long Meng; Tifei Yuan; Lili Niu; Hairong Zheng (IEEE, 2024)
Given the widespread occurrence of obesity, new strategies are urgently needed to prevent, halt and reverse this condition. We proposed a noninvasive neurostimulation tool, ultrasound deep brain stimulation (UDBS), which can specifically modulate the hypothalamus and effectively regulate food intake and body weight in mice. Fifteen-min UDBS of hypothalamus decreased 41.4% food intake within 2 hours. Prolonged 1-hour UDBS significantly decreased daily food intake lasting 4 days. UDBS also effectively restrained body weight gain in leptin-receptor knockout mice (Sham: 96.19%, UDBS: 58.61%). High-fat diet (HFD) mice treated with 4-week UDBS (15 min / 2 days) reduced 28.70% of the body weight compared to the Sham group. Meanwhile, UDBS significantly modulated glucose-lipid metabolism and decreased the body fat. The potential mechanism is that ultrasound actives pro-opiomelanocortin (POMC) neurons in the hypothalamus for reduction of food intake and body weight. These results provide a noninvasive tool for controlling food intake, enabling systematic treatment of obesity.